The promotion of accessibility and the inclusion of people with disabilities in the labor market – research in a Federal Public Institution: pesquisa em uma Instituição Pública Federal (Revista Educação, Artes e Inclusão, 2025)
This article is part of the field of study of social inclusion of people with disabilities and aimed to verify compliance with accessibility criteria for inclusion in the labor market, through field research undertaken in a Federal Public Institution. Six closed-ended questionnaires adapted from the Accessibility Self-Assessment Instrument (JANUZZI et al., 2019) were used, answered by the managers responsible for the following areas in the Institution: Institutional Planning, Infrastructure, Organizational Communication, Logistics, Information Technology and Management of People. A descriptive analysis of the data obtained individually for each dimension of accessibility was carried out, in which it was observed that the accessibility criteria were met according to the prioritization established by Januzzi et al. (2019). It was concluded that, although the absolute compliance with the normative criteria required for the promotion of accessibility is still considered complex, the more there is progress in this sense, the reduction of barriers imposed on people with disabilities will proportionally occur so that the work environments, as well as any other social space, can become more egalitarian and inclusive.
Keywords: accessibility; inclusion in the labor market; people with disabilities; federal public institution